Good way to keep an idiot busy for a couple of hours.

cos^{2}x + sin^{2}x = 1 is the trigonometric form of the Pythagorean theorem

cos^{2}x + sin^{2}x = 1

cos^{2}x = 1 – sin^{2}x

cos x = (1 – sin^{2}x)^{1/2}

1 + cos x = 1 + (1 – sin^{2}x)^{1/2}

(1 + cos x)^{2} = (1 + (1 – sin^{2}x)^{1/2})^{2}

for x = π (pi = 3,14159265…), we have,

(1 – 1)^{2} = (1 + (1 – 0)^{1/2})^{2}

0 = (1 + 1)^{2}

0 = 4 //interesting ?!

no this is bullshit

sqrt(cos^2(x))=abs(cos(x)) not just cos(x)

“a

sophismis a confusing or slightly incorrect argument used for deceiving someone”